THE CONCEPT OF RELIGIOUS MODERATION OF MUSLIM MINORITY COMMUNITY IN CHARACTER BUILDING OF WEST PAPUA SOCIETY - Chalik , Sitti Aisyah (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: Religious moderation is essential for all levels of society, especially students in West Papua City and Regency. This study was conducted to analyze the perceptions and constraints faced by students on the concept of religious moderation of Muslim minority communities in character building in West Papua. This qualitative research intended to explore the phenomenon experienced by the research subjects using methodological and scientific approaches. The data collection method was carried out through observation, interview, and documentation with researchers as the main instrument and supporting instruments using an observation list (checklist), interview guidelines, and media. The results showed that from the point of social relations, ordinary Muslim communities carry out activities blending with the communities, both non-Muslims and fellow Muslims. Abstrak: Moderasi beragama sangat penting bagi seluruh lapisan masyarakat khususnya mahasiswa yang berada di Kota dan Kabupaten Papua Barat.Penelitian ini dilakukan untuk menganalisis persepsi serta kendala yang dihadapi mahasiswa terhadap Konsep moderasi beragama masyarakat minoritas muslim dalam pembentukan karakter di Papua Barat.Penelitian ini merupakan penelitian kualitatif yang bermaksud untuk memahami fenomena tentang apa yang dialami oleh subjek penelitian, dengan pendekatan yakni dari segi pendekatan metodologis dan dari segi pendekatan keilmuan. metode pengumpulan data dilakukan melalui kegiatan observasi, wawancara, dan dokumentasi dengan peneliti sebagai instrument utama serta instrument penunjang berupa: daftar observasi (check list observation), pedoman wawancara, dan media. Hasil penelitian menunjukkan bahwa dari sudut hubungan sosial masyarakat muslim biasa melakukan kegiatan yang merupakan pembauran dengan masyarakat nonmuslim sekitar baik itu sesama muslim maupun yang lain.